The Influence of Online Customer Review (OCR) and Live Streaming on Purchase Decisions at Mygallerystore Via E-Commerce Shopee With Trust as an Intervening Variable - Elis, Elis (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2024)
This research aims to analyze the influence of online customer reviews (OCR) and live streaming on purchasing decisions at Mygallerystore via Shopee e-commerce with trust as an intervening variable. This research is causal associative with a quantitative approach. The research population of Shopee users who know and follow the Shopee Mygallerystore account with a sample of 150 samples selected using a purposive sampling technique. The data collection technique uses a questionnaire in the form of a Likert scale. Data processing in this research uses SmartPLS software version 4. The results of the research show that online customer reviews (OCR) have a significant influence on Trust, live streaming has a significant influence on Trust, the influence of online customer reviews on purchasing decisions has a significant influence, the influence of live streaming on Decisions purchasing is significant and positive, the influence of Trust on Purchasing Decisions is significant and positive, the indirect influence of online customer reviews on purchasing decisions through trust is significant, finally the results of the analysis show that live streaming on purchasing decisions through trust has a significant influence.